2021
DOI: 10.1002/tee.23462
|View full text |Cite
|
Sign up to set email alerts
|

DC Arc Resistance Rise by PMMA Cylinder Ablation with Arc Shrinking in Silica Sand Filling Space

Abstract: Concerning DC arc quenching phenomenon in silica sand filling space, we have proposed a new method for raising an arc column resistance (r col ) by use of polymer-material arrangement. This paper reveals physical factors for r col rise on the bases of experimental results using the following cylinders made of: (i) Quartz (SiO 2 ) and (ii) PMMA ((C 5 H 8 O 2 ) n ) with various inner diameters φ. For φ = 2 mm case, r col measured for a PMMA cylinder arrangement indicated higher r col at low current region, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Therefore, it is necessary to develop new DC arc quenching medium for further rise in rarc$$ {r}_{\mathrm{arc}} $$. In addition, we also found an arrangement of polymer material with the silica‐sand successfully increases rarc$$ {r}_{\mathrm{arc}} $$ [9–11]. This rise in rarc$$ {r}_{\mathrm{arc}} $$ can be interpreted based on improvement of ρ$$ \rho $$ due to the polymer vapor admixing into the Cu/SiO 2 vapor mixture.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, it is necessary to develop new DC arc quenching medium for further rise in rarc$$ {r}_{\mathrm{arc}} $$. In addition, we also found an arrangement of polymer material with the silica‐sand successfully increases rarc$$ {r}_{\mathrm{arc}} $$ [9–11]. This rise in rarc$$ {r}_{\mathrm{arc}} $$ can be interpreted based on improvement of ρ$$ \rho $$ due to the polymer vapor admixing into the Cu/SiO 2 vapor mixture.…”
Section: Introductionmentioning
confidence: 91%
“…The formed vapor is admixed into the arc. The role of the arc quenching medium in the gas phase is to increase r arc to reduce the fault current, as [15,16,18,22,23] Ceramic 1973 (melting) 10 14 12.0-30.0 3.90 ZrO 2 [15,16,18,24] Ceramic 2954 (melting) 10 12 1.7-3.0 5.68 AlN [15,16,18,25,26] Ceramic 2500 (melting) 10 13 3.0-180 3.26 Si 3 N 4 [15,16,18,[26][27][28] Ceramic 2173 (melting) 10 12 10.0-100.0 3.11 depicted in figure 1. To increase r arc , an increase in the electrical resistivity ρ R of the arc, shrinkage of an arc diameter d arc , or arc length l arc elongation are necessary.…”
Section: Selection Based On Roles In Arc Quenching Process: Gas-phase...mentioning
confidence: 99%
“…The authors group have studied a novel arc quenching medium which has higher arc quenching performance compared to flattery SiO 2 sand. For example, we successfully found that an additive of the polymer material with the SiO 2 sand increases r arc during the arc quenching process [11][12][13][14]. However, this method not only has advantages such as r arc increasing, but also the disadvantage of the decaying of R ins during the post-arc interruption process.…”
Section: Introductionmentioning
confidence: 99%
“…A re-solidified byproduct is known to form between electrodes during the arc quenching process in the filling SiO 2 sand. The formed byproduct is called 'fulgurite' [1,22,25]. In this experiment, the fulgurite produced between the electrodes in the model electric fuse was observed after the fuse operation to determine the fulgurite aspect for each condition.…”
Section: Observation Of Produced Fulguritementioning
confidence: 99%
“…The SiO 2 sand used as an arc quenching medium in the electric fuse has contributed to a rise in the transient arc column resistance r col to reduce the DC, and has eventually achieved a shorter arc quenching time for performing breaking of the DC. However, a further increase in the breaking ability of the electric fuse is expected in industrial fields, especially in DC distribution used in recent electric vehicles [22].…”
Section: Introductionmentioning
confidence: 99%